Teachers’ and Learners’ Perceptions of the Use of Science Content Songs in the Teaching and Learning of Ionic Bonding - Omollo, D. O.; Massam, W. E. (International Journal of Learning and Development, 2024)
Factoring learner engagement during chemistry lessons is key if conceptual understanding is an objective. This qualitative action research study explored the possibility of using science content songs to enhance learners’ engagement, motivation and interest in ionic bonding and related chemistry concepts among high school learners in Kenya. The study aimed at transforming learner attitudes in chemistry through songs as pedagogies and making them active participants during chemistry lessons. Two chemistry teachers and 65 form two students were purposively chosen to participate in the study. Out of the 65 students, 8 were selected through a random sampling method to participate in a focus group discussion. Data collection was conducted through multiple methods which included; lesson observation, interview, and focus group discussion. It was found that songs engaged learners throughout the lesson, captured their attention, enhanced their recalling abilities, and had the potential to restore their positive attitudes towards chemistry. Additionally, findings revealed that songs enhanced diverse learner preferences and extended learning outside the classroom. The study recommends that schools should consider the use of songs as a classroom instructional strategy due to its high potential to engage learners and spark learners’ interest in chemistry learning.